Agronomic performance of soybeans with the presence of volunteer RR corn - Ferronato, Samuel Josué; Canepelle, Eduardo; Drescher, Marta Sandra; da Silva, Danni Maisa; Redin, Marciel (Revista Ceres, 2022)
The presence of volunteer corn plants among soybeans, both resistant to glyphosate, has increased in recent years in Brazil. The objective of this study was to quantify the impact on the agronomic performance in RR soybeans by the presence of volunteer RR corn in field conditions. The experiment was conducted in Tiradentes do Sul (RS), 2018/19 harvest. The experimental design used in the experiment was randomized blocks with four replications: control in the clean (only soybean) and eight densities of volunteer corn in soybean crop with 1, 2, 3, 4, 5, 6, 7 and 8 corn plants m-2. In the physiological maturation of soybean, plant height, number of lateral branches, stem diameter, height of insertion of the first pod, number of pods plant-1 and grain yield were evaluated. All variables analyzed were negatively affected by the increase in the density of volunteer corn infestation, where the variables grain yield and number of pods plant-1 were the most affected, 63% and 81%, respectively. The presence of volunteer corn has a high capacity to reduce the yield of soybeans in the proportion of 500 kg ha-1 plant-1 of corn m-2, and even at low densities, it needs control.